International perspectives on arts and dementia research - Lopez Quiroga, Maria (Arte, Individuo y Sociedad, 2017)
Review on the symposium for Arts and Dementia Research that took place between the 16th and 20th November 2016, at the Gerontological Society of America’s Annual Scientific Meeting.